Intervention strategy for concentration of attention on fencers (Original) (Revista científica Olimpia, 2020)
The research was carried out at the Comprehensive Sports School (EIDE): Pedro Batista Fonseca de Granma with 20 children who practice fencing, aged between twelve and fourteenyears. A study was carried out of the characteristics of the behavior of the children, which are expressed in sports training. The results obtained through the diagnosis and characterization of the subjects show a high incidence of attention deficit and hyperactivity disorders (ADHD) and determine the need to design intervention strategies to favor the concentration of attention in school fencing athletes to starting from training, which positively influences the development of the capacity for sustained attention, concentration, speed and perceptual acuity, as well as resistance to fatigue, an essential element for the development of the quality of tactical execution, at school.
Keywords: intervention strategy; fencing; attention deficit hyperactivity disorder.